2020
DOI: 10.1038/s41598-020-59170-5
|View full text |Cite
|
Sign up to set email alerts
|

Couples with mild male factor infertility and at least 3 failed previous IVF attempts may benefit from laparoscopic investigation regarding assisted reproduction outcome

Abstract: the aim of this study is to assess the value of laparoscopy for couples diagnosed with mild male factor infertility and at least three previous failed In-Vitro Fertilization (IVF) attempts. A total of 169 couples were included in this prospective cohort study. patients were presented with the option of being subjected to laparoscopic investigation for correction of previously unidentified endometriosis or pelvic adhesions. The outcome measures were Live Birth/Ongoing Pregnancy, clinical pregnancy and positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…NICE guidelines do not comment on the usefulness of laparoscopic surgery prior to IVF treatment in order to improve IVF outcomes [ 101 ]. However, studies performed in the Greek population provide data indicating that undiagnosed endometriosis could be underlying behind unexplained infertility, and laparoscopic diagnosis and correction of underlying pathologies could significantly improve reproductive outcome of these patients [ 1 , 2 ]. Considering the aforementioned, it is unclear which treatment strategy could improve oocyte and embryo quality improving reproductive system functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NICE guidelines do not comment on the usefulness of laparoscopic surgery prior to IVF treatment in order to improve IVF outcomes [ 101 ]. However, studies performed in the Greek population provide data indicating that undiagnosed endometriosis could be underlying behind unexplained infertility, and laparoscopic diagnosis and correction of underlying pathologies could significantly improve reproductive outcome of these patients [ 1 , 2 ]. Considering the aforementioned, it is unclear which treatment strategy could improve oocyte and embryo quality improving reproductive system functionality.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that where endometriosis-related infertility is concerned, the asymptomatic nature of the underlying disorder complicates things. This harbors the risk of a false unexplained infertility diagnosis and subsequent futile in vitro fertilization (IVF) attempts [ 1 , 2 ]. It is estimated that 30–50% of women with endometriosis are infertile [ 3 ], while it has been suggested that 20–50% of subfertile women are diagnosed with endometriosis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Newer studies suggest that laparoscopic surgery as an investigative and corrective tool of the underlying pathologies prior to initiating numerous and various therapeutic attempts, should be taken into consideration for women suffering from unidentified infertility etiology, as it can greatly impact the outcome, as well as improving the overall costs of the lengthy treatment plan and ultimately the quality of life of the women going through this journey towards child conceiving [ 181 ]. The same view on laparoscopic investigation prior to concentrating on assisted reproduction techniques is shared when focusing on mild male factor infertility cases, especially if previous failed IVF have attempts attributed to an infertility etiology [ 182 ].…”
Section: Therapeutic Options Available For Endometriosis-associatementioning
confidence: 99%